Endothelial Cells as a Key Cell Type for Innate Immunity: A Focused Review on RIG-I Signaling Pathway - Xu, Suowen; Jin, Tengchuan; Weng, Jianping (Frontiers in Immunology, 2022)
The vascular endothelium consists of a highly heterogeneous monolayer of endothelial cells (ECs) which are the primary target for bacterial and viral infections due to EC’s constant and close contact with the bloodstream. Emerging evidence has shown that ECs are a key cell type for innate immunity. Like macrophages, ECs that acts sentinels when sensing invading pathogens or microbial infection caused by viruses and bacteria. It remains elusive how ECs senses danger signals, transduce the signal and fulfil immune functions. Retinoic acid-inducible gene-I (RIG-I, gene name also known as DDX58) is an important member of RIG-I-like receptor (RLR) that functions as an important pathogen recognition receptor (PRR) to execute immune surveillance and confer host antiviral response. Recent studies have demonstrated that virus infection, dsRNA, dsDNA, interferons, LPS, and 25-HC can increase RIG-1 expression in ECs and propagate anti-viral response. Of translational significance, RIG-I activation can be inhibited by Panax notoginseng saponins, endogenous PPARγ ligand 15-PGJ2, tryptanthrin and 2-animopurine. Considering the pivotal role of inflammation and innate immunity in regulating endothelial dysfunction and atherosclerosis, here we provided a concise review of the role of RIG-I in endothelial cell function and highlight future direction to elucidate the potential role of RIG-I in regulating cardiovascular diseases as well as virus infectious disease, including COVID-19. Furthered understanding of RIG-I-mediated signaling pathways are important to control disorders associated with immune and inflammation.